Pengaruh Kemampuan Manajerial dan Supervisi Kepala Madrasah Terhadap Kinerja Guru - Muniroh, Siti; Soedjarwo, Soedjarwo; Roesminingsih, Erny (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2022)
The managerial and supervisory abilities of the islamic school principal play an important role on improving teacher performance to realize the quality of education. The purpose of this study is to find out how much the influence of managerial and supervisory abilities of madrasah principal on the performance of islamic junior high school teachers in Manyar district. This research uses a quantitative approach with the type of correlational research. The data collection method uses two techniques, namely documents and unstructured interviews. The results of the study showed that there is a significant effect of the manegerial and supervisory abilities of islamic school principal on the performance of islamic junior high school teachers in Manyar district. It can be concluded that there is an influence between managerial and supervisory abilities of islamic school principal on the performance of islamic junior high school teachers in Manyar Gresik district Key words: Managerial Ability, Supervision,Teacher Performance Abstrak: Kemampuan manajerial dan supervisi kepala madrasah memegang peranan penting terhadap peningkatan kinerja guru untuk mewujudkan mutu pendidikan.Tujuan dari penelitian ini adalah untuk mengetahui besarnya pengaruh kemampuan manajerial dan kemampuan supervisi kepala madrasah terhadap kinerja guru madrasah tsanawiyah di kecamatan Manyar. Penelitian ini menggunakan pendekatan kuantitatif, dengan jenis penelitian korelasional. Metode pengumpulan data menggunakan dua teknik yaitu dokumen dan wawancara tidak terstruktur. Hasil penelitian terdapat pengaruh signifikan kemampuan manajerial dan supervisi kepala madrasah terhadap kinerja guru madrasah tsanawiyah di kecamatan Manyar. Hal ini dapat disimpulkan ada pengaruh antara kemampuan manajerial dan supervisi kepala madrasah terhadap kinerja guru madrasah tsanawiyah di kecamatan Manyar Gresik.   Kata kunci: Kemampuan Manajerial, Supervisi, Kinerja Guru.